Regulation of Compensation for Victims By Perpetrators of Traffic Accidents Accroding to Law number 22 Year 2009 on Road Traffic and Trasportation - Putri, Debi Riski Aulia; Sukmareni, Sukmareni (Asosiasi Ide Bahasa Kepri, 2025)
The purpose of this article is to examine the provisions of Law No. 22 of 2009 that govern victims' compensation in the event of a traffic accident. In order to hasten the progress that will be made in society, traffic is a crucial mode of communication. The four primary causes of traffic accidents include elements related to nature, humans, roads, and vehicles. Most traffic accidents are caused by human error, therefore everyone, particularly the elderly, has to be extra careful on the road. Drivers are liable for damages caused by their illegal acts if another person is injured or dies as a result of their carelessness or negligence, as stated in Article 234 and 235 of Law No. 22 of 2009 about traffic and road transportation. Research in this publication that adheres strictly to stated rules is known as the normative approach. Reading, quoting, and studying documents such as legislation, journals, or other internet media constitute primary and secondary legal materials that the author employs in this work. Primary materials include those that pertain to Law No. 22 of 2009, while secondary materials include a variety of books, journals, and online sources. The author also conducts library studies to gather data. This study's findings clarify the distinction between traffic penalties and compensation, as well as the kind of legislation governing compensation